Rare ocular toxicity induced by pertuzumab/QL1209 in healthy chinese subjects: case reports and whole-exome sequencing analysis - Ma, Junlong; Chen, Wenjing; Hu, Zhanqing; Huang, Jie; Guo, Chengxian; Zou, Chan; Yang, Guoping (Investigational new drugs, 2022)
Summary Pertuzumab is a recombinant anti-HER2 humanized monoclonal antibody widely used for the adjuvant treatment of HER2-positive breast cancer. Its safety is well established with the most common adverse effects being diarrhea and rash. To our knowledge, severe pertuzumab-induced ocular adverse events have never been reported. Herein, we describe several cases of pertuzumab/QL1209 (pertuzumab biosimilar)-induced blurred vision in healthy Chinese male subjects after a single injection of 420 mg pertuzumab/QL1209. Persistent optic nerve damage and vision loss occurred in the most severe case even after ophthalmic treatment. We conducted whole-exome sequencing (WES) of DNA samples from 5 cases and 13 controls to analyze the potential genetic factors and identified some associated variants (rs80303690 in RBM24 , rs117375173 in CASR , rs1805097 in IRS2 , and rs1227049 in CDH23 ). Furthermore, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways and Gene Ontology (GO) terms gene enrichment analyses were carried out for differentially expressed genes clustered in the PI3K/AKT/mTOR and Ras/Raf/MAPK signaling pathways, which were exactly activated by HER2 phosphorylation. In summary, this is the first report describing the occurrence of ocular toxicity induced by pertuzumab in the Chinese population and exploring the possible genetic mechanisms. These findings could provide evidence for clinicians to raise concerns about the risk of ocular toxicity with the clinical use of pertuzumab.